On the Exploration of the Tri Hita Karana Belief as Balinese Local Wisdom in Tangis Pertiwi Song Lyric - Darmayuda, Komang; Netra, I Made (Journal of A Sustainable Global South; Vol 3 No 1 (2019): February 2019DO - 10.24843/jsgs.2019.v03.i01.p06, 2019)
A song, one of the literary works and arts, is full of the contents of the values of the local wisdom of the community, because its creation is usually based on factual phenomena that are happening in the community. This article aims to see the implementation of Tri Hita Karana belief as the local wisdom of Balinese people in Balinese songs entitled Tangis Pertiwi. This song was comprehensively observed and recorded to be analyzed by qualitative methods with a descriptive approach. The results of data analysis show that the song Tangis Pertiwi has a thematic structure, namely harmony supported by schematic structures that are systematically arranged in song verse, such as the harmonious relationship between humans and nature implied in the first verse, between humans and humans in the second verse, and humans with God Almighty in the third verse. Viewed from the dimensions of cultural meaning, the song Tangis Pertiwi contains moral values in the form of advice and suggestion to always follow the Tri Hita Karana belief, and the norm of apology   if something happens outside the belief; the Balinese character is harmonious, humble, alert, forgiving; the symbolic meanings contained in this song are beautiful, safe, sharing, guarding; finally the moral message is literal-indirectly delivered. Whereas in Bali there were many actions that were no longer carried out to enforce Bali, including disobeying Tri Hita Karana belief. Therefore, it is time for Balinese people to apologize to God the Almighty and promise not to do things outside the Tri Hita Karana belief. Index Terms — exploration, Tri Hita Karana, Tangis Pertiwi, harmonious, Balinese